Role of Nitrous Oxide Inhalation Sedation in Minor Periodontal Surgery – A Pilot study - Chopra, Rahul; Mathur, Shivani; Sharma, Nikhil; Sachdev, Vinod; Pal, Chandan (Journal of Orofacial Research, 2020)
Background and objective: Alleviation of patient’s anxiety and pain during periodontal surgical procedures is a major concern in the field. Amongst the various modalities used till date, inhalation sedation has gained attention in recent times. Thus the present study evaluates the effectiveness of inhalation sedation for better acceptance of minor periodontal surgical procedures. Methods: In this split mouth study, patients with chronic periodontitis were divided into two groups. Gingival curettage was performed under Local Anaesthesia (LA) in group 1, while in group 2 gingival curettage was performed on contra-lateral site under LA as well as inhalation sedation. Saturation of Peripheral Oxygen (SpO2) and pulse rate were recorded at baseline, during procedure and after procedure from both the groups. Visual Analogue Scale (VAS) for pain during procedure was also recorded. Results: Pulse rate values decreased and improved SpO2 values were observed in group 2 compared to group 1 thereby indicating decreased anxiety levels in the former. Further The VAS scores for pain experienced during the procedure were better in group 2. Conclusion: In anxious patients undergoing minor periodontal surgical procedures Nitrous oxide inhalation sedation can be used for better management of pain perception and decreasing anxiety levels.